Winter’s Walk: All the Light I Hold in This Moment (LEARNing Landscapes, 2020)
How do we enlarge the space of the possible to encourage our students to notice the educational, social, economic, communal, and political scripts that perform us? Academic performance imagines new ways of performing research. Conventional academic performances have been interrupted. Be aware. We can never take for granted the performance that is us. I want to be awakened to the gaps and absences in the performances that our students offer us, as we create space for them to perform in our classrooms, on school stages, in our hearts. How might performance become an action site of resistance, of resolution, of advocacy, of invitation, of renewal?